The Impact of Major and Minor Phytocannabinoids on the Maintenance and Function of INS-1 β-Cells Under High-Glucose and High-Lipid Conditions - Esmaeel Ghasemi Gojani; Bo Wang; Dong-Ping Li; Olga Kovalchuk; Igor Kovalchuk (Molecules, 2025)
Type 2 diabetes mellites (T2DM) is the most common form of diabetes and affects a significant portion of the population. Obesity-related increases in free fatty acids and glucose in the diet contribute to β-cell dysfunction and loss, ultimately leading to the onset of T2DM. The endocannabinoid system, which is present throughout the body, plays a vital role in regulating various physiological processes, including those in the pancreas. This system has been implicated in metabolic disorders like obesity and diabetes, as it helps to regulate appetite, food intake, and fat production. Phytocannabinoids from Cannabis sativa have the potential to influence the endocannabinoid system, offering a promising therapeutic approach for diabetes and its complications. Using high-glucose–high-lipid (HGHL)-induced INS-1 β-cells, we investigated the protective effects of two major (THC and CBD) and three minor (THCV, CBC, and CBG) phytocannabinoids on high glucose–high lipid (HGHL)-induced apoptosis, cell cycle disruption, and impaired function of beta-cells. Our results showed that all five phytocannabinoids reduced HGHL-induced apoptosis, likely by decreasing TXNIP protein levels. Additionally, THC and all three minor phytocannabinoids provided protective effects against functional impairments caused by HGHL exposure.